AB1147 Treatment of blau syndrome-related uveitis with the long-acting IL-1 inhibitor CANAKINUMAB: 6 months follow-up. (23rd January 2014) - Simonini, G.; Pagnini, I.; De Libero, C.; Giani, T.; Caputo, R.; Cimaz, R.
Abstract : Background: Pediatric granulomatousarthritis is a very rare conditionthataffectsyoung children and is characterized by the triad of exudative tenosynovitis, maculopapular rash, and uveitis. A genetic form, known as Blau syndrome (BS) is associated with mutations in the NOD2/CARD15 gene. Prognosis is severe, with sight-threatening uveitis occurring in many cases, and treatment has been so far unsatisfactory. Biologic treatment with IL-1 inhibitors has been tried in classic autoinflammatory diseases, but rarely in BS. Objectives: To report the clinical response to canakinumab of a BS patient with sight-threatening uveitis, resistant to different treatments Results: A 4 year old boy was diagnosed with BSfor the typical clinical features, histologic evidence of non-caseating granulomas, and a NOD2 mutation (R334W, in heterozygosis ) . Arthritis and rash subsided over time, but bilateral panuveitis progressed since the age of 5 years, and was initially treated with methotrexate. Because of the persistent ocular inflammation, resistent to high steroid doses and eventually leading to progressive visual impairement, at the age of 10 Infliximab was added. After an initial improvement, uveitis worsened and at the age of 12 Infliximab was switched to Adalimumab without any improvement. Mycophenolate mofetil, and then Abatacept were sequentially administered, with no significant positive effects. At the age 16, the boy still had granulomatous retinal lesions, anterior chamber inflammation, and occasional macular edema that led to retinal detachment at the age of 16. Steroid pulses- 3 bolus/month for 6 consecutive months - were necessary to control disease flares. On the basis of the supposed autoinflammatory nature of BS, we then decided to start IL-1 antibody administration: Canakinumab, 2 mg/kg/month.At 6 months follow-up without concomitant treatment modifications, no ocular flares had occurred, no steroid pulses were necessary, and uncorrected visual acuity was 9/10. Canakinumab was well tolerated. Conclusions: We report for the first time clinical response of BS-related uveitis to Canakinumab. Although this represents only one case and the prognosis can be variable, the progressive nature of the disease and the unresponsiveness to all other treatments makes us confident on the possible efficacy of this drug. A longer follow-up is however necessary to draw firm conclusions References: Fink CW, Cimaz R Early onset sarcoidosis: not a benign disease. J Rheumatol. 1997, 24: 174-177. Cimaz R, Ansell BM, Sarcoidosis in the pediatric age. Clin Exp Rheumatol. 2002, 20:231-7. Arόstegui JI, Arnal C, Merino R, et al. NOD2 gene-associated pediatric granulomatous arthritis: clinical diversity, novel and recurrent mutations, and evidence of clinical improvement with interleukin-1 blockade in a Spanish cohort. Arthritis Rheum. 2007, 56:3805-13. Rosè C, Arostegui J, Martin T, et al. NOD2-Associated Pediatric Granulomatous Arthritis, an expanding phenotype. Arthritis Rheum. 2009;60: 1797-1803. Disclosure of Interest: None Declared